A self-assembled metamaterial for Lamb waves - Khanolkar, Amey; Wallen, Samuel; Ghanem, M. Abi; Jenks, J.; Vogel, Nicolas; Boechler, N. (Applied Physics Letters, 2015)
We report the design and characterization of a self-assembled, locally resonant acoustic metamaterial for Lamb waves, composed of a monolayer of 1.02 extgreekmm polystyrene microspheres adhered to a 1.27 extgreekmm thick free-standing silicon membrane. A laser-induced transient grating technique is used to generate Lamb waves in the metamaterial and to measure its acoustic response. The measurements reveal a microsphere contact resonance and the lowest frequency spheroidal microsphere resonance. The measured dispersion curves show hybridization of flexural Lamb waves with the microsphere contact resonance. We compare the measured dispersion with an analytical model using the contact resonance frequency as a single fitting parameter, and find that it well describes the observed hybridization. This study may lead to an improved understanding of microscale contact mechanics and to the design of new types of acoustic metamaterials.